Improved DCFR protocol for path recovery in mobile ad-hoc networks - Kaur, Rupinder; Singh Kang, Sandeep (International Journal of Engineering and Technology, 2018)
The mobile ad-hoc network is the decentralized type of network in which mobile nodes can move from one location to another. Due to random mobility of the mobile nodes route establishment, route maintenance is the major issues of mobile ad-hoc networks. This research paper, focus on the route establishment and route maintenance properties of mobile ad-hoc network. The DCFR protocol is the route establishment and route maintenance protocol in which broker route will be recovered on the basis of node connectivity. The node, which has maximum connectivity, is selected as the best node for route recovery in DCFR Protocol. In this research work, the DCFR protocol is further improved by adding buffer size parameter for route recovery which also maintains quality of service in the network. The proposed DCFR protocol simulation results perform well as compared to existing DCFR protocol in terms of certain parametersÂ Â